Enhanced neurogenesis in the hippocampal dentate gyrus during antigen-induced arthritis in adult rat--a crucial role of immunization. - Johannes Leuchtweis; Michael K Boettger; Fanny Niv; Christoph Redecker; Hans-Georg Schaible (PLoS ONE)
Neurogenesis in the subgranular zone of the mammalian hippocampal dentate gyrus contributes significantly to brain neuroplasticity. There is evidence that inflammation of the central nervous system inhibits neurogenesis but peripheral inflammation such as antigen-induced arthritis may rather enhance neurogenesis. Manifest arthritis is associated with symptoms such as pain and altered locomotion indicating that peripheral inflammation is associated with changes of both the immune system and the nervous system. This raises the intriguing question whether immune or neuronal factors or both actually drive changes of neurogenesis. Here we explored hippocampal neurogenesis in the rat during chronic antigen-induced arthritis in the knee joint. We analyzed neurogenesis in control rats, and in rats which were immunized for the antigen producing arthritis but which did not show arthritis and neurological symptoms, and in rats in which antigen injection into the knee produced manifest local inflammation and symptoms such as pain at the inflamed knee and altered locomotor behavior. Neurogenesis was assessed by quantifying bromodeoxyuridine-positive cells in sections of the complete hippocampal dentate gyrus. Compared to control animals, rats with antigen-induced arthritis presenting manifest local inflammation, hyperalgesia at the inflamed knee and significantly altered locomotion exhibited a significant increase of bromodeoxyuridine-positive cells. However, a similar increase in the number of such cells was found in rats which were only immunized against the antigen, but in which no local inflammatory response was induced and which thereby neither showed hyperalgesia nor alterations of locomotion. Thus we conclude that in peripheral immune-mediated arthritis the activation of the immune system in the process of immunization is the causal factor driving enhanced neurogenesis, and neither the local enhancement of inflammation nor the activation of the nervous system leading to neurological symptoms such as pain and altered locomotion. It seems noteworthy to further explore the clinical importance of this neuroimmune interaction.